Bacillus coagulans regulates gut microbiota and ameliorates the alcoholic-associated liver disease in mice - Liu, Zhen z.; Liu, Tong; Zhang, Zhen t.; Fan, Yu r. (Frontiers in Microbiology, 2024)
Alcoholic-associated liver diseases (ALD) are now widespread issues worldwide. Alcoholic-induced chronic dysbiosis of the gut microbiota is one of the factors in the pathophysiology of ALD. Our findings demonstrate that hepatic inflammatory injury damage and accumulation of fat can be effectively reduced in mice with ALD by altering the gut microbiota utilizing Bacillus coagulans. Treatment with B. coagulans significantly modulates the levels of TNF-α, IL-1β, and IL-22 cytokines while maintaining tight junction proteins and mucin protein expressions to support intestinal barrier function restoration. Treatment with B. coagulans also alters the composition of the gut microbiota and increases the production of short-chain fatty acids (SCFAs). This is mostly due to B. coagulans promotes the growth of bacteria that produce SCFAs, such as Ruminococcus species and Akkermansia, while inhibiting the growth of pathogenic bacteria like Escherichia Shigella. Moreover, treatment with B. coagulans causes levels of 2-Ketobutyric acid, ketoleucine, and indoleacetic acid increase while homovanillic acid and 3'-O-Methylguanosine metabolites decrease significantly. This study facilitates the development of therapeutic and preventive strategies for ALD using lactic acid bacteria.